Children's Rights in Islamic Law and International Conventions: Comprehensive Protection from Cradle to Adulthood - Nours Issa Al-Malham, (International Journal of Law Research and Studies, 2026)
The research aimed to present children's rights in Islamic law and international conventions, with reference to the stages in which children's rights are declared and protected as comprehensive protection from cradle to adulthood. To achieve the research's objectives and goals, the descriptive-analytical approach and the comparative approach were adopted, given their suitability to the research topic and its context. Several Arab and foreign sources and references were consulted in preparing this research. A number of different conclusions were reached, the most prominent of which are: Islam, with its principles in the field of human rights and childcare, preceded positive legislation and international agreements, which emerged hundreds of years later, confirming in some of their foundations and principles what Islam affirmed long ago. The Universal Declaration of the Rights of the Child is a global achievement by the United Nations in the field of human rights in general, and children's rights in particular. However, this achievement does not mean it is the first of its kind in human history, as some jurists claim. Islam, as the study demonstrates, preceded this declaration and other international human rights conventions by many centuries. The researcher also presented a number of recommendations, the most important of which are: the necessity of continuing research and studies and holding seminars and conferences on the subject of children's rights, as it is an open forum for suggestions and efforts, and strengthening the status of children as persons with full rights in society, which instills in the souls of young people self-confidence and a sense that they are a respected entity whose rights are protected.
Keywords: Children's Rights; Islamic law; International Conventions